2013
DOI: 10.1039/c3nr32979h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of magnetically induced linear aggregates on proton transverse relaxation rates of aqueous suspensions of polymer coated magnetic nanoparticles

Abstract: It has been recently reported that for some suspensions of magnetic nanoparticles the transverse proton relaxation rate, R(2), is dependent on the time that the sample is exposed to an applied magnetic field. This time dependence has been linked to the formation of linear aggregates or chains in an applied magnetic field via numerical modeling. It is widely known that chain formation occurs in more concentrated ferrofluids systems and that this has an affect on the ferrofluid properties. In this work we examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 41 publications
1
45
0
Order By: Relevance
“…This critical temperature for a myristic acid sterically stabilized single core magnetite water based ferrofluid resulted to be 42.5ºC [55], a temperature close to the range of interest for live cell experiments. Phase condensation was found to have a negative influence on the effectiveness of magnetic nanoparticles' use as contrast agents in MRI [56] evidenced by` the influence of the magnetically induced linear chains in PEG coated single core particle dispersions on the proton transverse relaxation rates. It was found that the transverse relaxation rate diminishes with increasing particle chaining, i.e.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 2 more Smart Citations
“…This critical temperature for a myristic acid sterically stabilized single core magnetite water based ferrofluid resulted to be 42.5ºC [55], a temperature close to the range of interest for live cell experiments. Phase condensation was found to have a negative influence on the effectiveness of magnetic nanoparticles' use as contrast agents in MRI [56] evidenced by` the influence of the magnetically induced linear chains in PEG coated single core particle dispersions on the proton transverse relaxation rates. It was found that the transverse relaxation rate diminishes with increasing particle chaining, i.e.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…In both single core and multicore systems the magnetically induced condensation process may take minutes before reaching equilibrium [49,56]. It is worth mentioning that spontaneous clustering can also occur in both single core and multicore magnetic particle dispersions when the attractive forces (van der Waals, magnetic dipole-dipole) overcome the repulsive ones (steric, electrostatic) [56].…”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to Van der Waals attractive forces among the particles, anisotropic magnetic dipole interactions can play a role in the aggregation process. It was observed by several authors [11][12][13][14], that in applied magnetic field SPION or nanoparticles with encapsulated SPION form one-dimensional chainlike aggregates or self-assembled structures. It has also been reported that in diluted aqueous dispersions of surfactant-coated SPIONs, chainlike aggregates with the fractal dimension D = ~1.2 were formed spontaneously [10,15].…”
Section: Introductionmentioning
confidence: 94%
“…For example, magnetic polymer coated iron oxide NM form linear aggregates in the presence of a magnetic field, the structure of which have been examined by TEM imaging of sections of the aggregates captured in gel and resin-embedded for imaging. 62 Furthermore, scanning electron microscopy (SEM) has been used to investigate the dispersion of TiO 2 NM agglomerates in the presence of bacteria. 63 Analysis by TEM however must avoid using sample preparation involving dropping and drying a solution on a grid (the drop-cast method), since it induces NM agglomeration, negating quantitative sizing.…”
Section: Microscopy Techniquesmentioning
confidence: 99%